Problems in Prevention of Suicidal Behavior of Prisoners - DZHANSARAYEVA, Rima Yerenatovna; NURMAGANBET, Yermek Talantuly; ZHANIBEKOV, Akynkozha Kalenovich; TURGUMBAYEV, Marlen Yerlanovich; NABIYEV, Amirzhan Amirzhanovich (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
Suicide of convicts, their suicidal behavior counteracts implementation of the objectives of the penal system, primary of which are the protection of rights and legitimate interests of persons sentenced to imprisonment, maintenance of security, and provision of assistance in social adaptation. Therefore, a deep examination of the problems related to the prevention of suicides of prisoners and the prevention of their suicidal behavior is considered of great importance. The article analyzes the phenomenon of suicide, its nature, substance, essence; types of suicidal behavior and personality traits of prisoners who committed suicide in places of detention; recommendations on the improvement of organizational and legal measures to prevent suicide among persons sentenced to deprivation of liberty are being put forth.